Corona Lisa, or the Pandemic Mask Unveilings of Mona Lisa - Głażewska, Ewa; Karwatowska, Małgorzata (Papers in Linguistics, 2022)
The aim of this article is to analyze representations of Leonardo da Vinci’s famous Mona Lisa portrait that are depicted on anti-COVID masks and have been creatively developed through the use of motifs taken from pop culture texts. Around 4,000 images of masks retrieved from the Internet were examined. The focus was on both visual and linguistic aspects, showing the directions the ‘mask designers’ took, the motifs they referred to, and the techniques they used in an attempt to present their versions of Mona Lisa. In the first part of the article, the history of the famous painting is briefly presented; in the second part, subcategories within which masks can be analyzed are enumerated; then, the focus is on specific visual representations, including those that are difficult to classify in a clear and unequivocal manner. At the same time, references are made to wordplay and language games as means of creating new images of Mona Lisa (Corona Lisa, Covid Lisa etc.). Applying the method of content analysis, the intention of the research was to show the richness of “Mona-Lised” masks as a specific sign of the times of the COVID-19 pandemics.